THE DESCRIPTION OF ORAL AND DENTAL HEALTH CARE SERVICE IN PUSKESMAS I DENPASAR UTARA IN 2011 - I Gusti Ayu Pradnyadani (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
The implementation of oral and dental health care in community health centre (puskesmas) is holistic in nature, integrated, in form of promotive, preventive and curative efforts can he done both in the puskesmas as well as outside puskesmas building. The health care fororal and dental care in puskesmas starts from emergency care to professional level. Such types of health care includes:  basic emergency care, preventive care, self care and simple care. The objective of this research is to identify the data of  oral and dental health care request  in Puskesmas I Denpasar Utara in September 2011, using secondary data in the form of Registration Book of Patients Visits.The finding of this research is that the oral and dental health care request for the dental amalgam remains much higher in permanent teeth than those for deciduous teeth. The dental amalgam request for permanent teeth is at 95.1% , the deciduous teeth is at 4.9%. Endodontic treatment for permanent teeth is at 94,6%, and for deciduous teeth is at 5.4%. Medication of abscessby medicines permanent teeth is at 92.1%, and for deciduous teeth is at 7.9%. For the dental extractions for the deciduous teeth is at 70%, and for the permanent teeth is at 30%.Based on such finding, it can be concluded that the dental health care requests in Puskesmas I Denpasar Utara  in 201I, includes is majority for the permanent teeth.